Pendulone induces apoptosis via the ROS-mediated ER-stress pathway in human non-small cell lung cancer cells. (June 2022) - Cheng, Wen-Chien; Wen, Ya; Chiu, Yen-Shuo; Chou, Chia-Hao; Lim, Chen-Jen; Lin, Sheng-Hao; Chang, Jia-Ming; Lin, Chi-Chien
Abstract: Purpose: Pendulone, an isoflavone compound, is known to act against human cancer cells. However, its role in human non-small cell lung cancer (NSCLC) and the exact molecular mechanisms of action have never been reported. Methods: We investigated the effects of pendulone on cell proliferation and apoptosis in human NSCLC H1299 cells. Cell viability was examined using the methyl-thiazol-diphenyl-tetrazolium (MTT) assay. Flow cytometry was employed to evaluate apoptotic indices such as the cell cycle, mitochondrial membrane potential, cytochrome c release, caspase activity, and death receptor expression. The expression of proteins related to the cell cycle and apoptosis were analyzed by Western blot analysis. Results: Pendulone significantly decreased H1299 cell viability by inducing endoplasmic reticulum (ER) stress through the accumulation of reactive oxygen species (ROS). Pendulone induced the expression of ER stress-associated proteins, such as ATF4 and CHOP, which promoted the expression of death receptors. Activation of caspase 8 induced extrinsic pathway apoptosis. Pendulone also caused the loss of mitochondrial membrane potential, inhibited the anti-apoptotic proteins BCL-2 and activated the pro-apoptotic protein BAX, which promoted the release of cytochrome c to activate caspase 9. Antioxidant N -acetylcysteine (NAC), with its ROS-suppressive property, reversed pendulone-induced ER stress and cell apoptosis. Conclusion: Our findings provide evidence that pendulone induces apoptosis by inducing ER stress through ROS accumulation and mitochondrial dysfunction in NSCLC cell lines. Highlights: Pendulone decreases cell viability by inducing ER stress through the accumulation of ROS. Pendulone induces ER stress, which promoted the extrinsic pathway involves the activation of death receptors. Pendulone induces mitochondria-associated intrinsic apoptosis pathways. Antioxidant N -acetylcysteine, with its ROS-suppressive property, reverses pendulone-induced ER stress and cell apoptosis.